ANALISIS ECONOMIC VALUE ADDED / EVA (Studi Analisis pada Perusahaan Manufaktur Sub Sektor Rokok di BEI) - Aryanti, Rahmi (Jurnal Manajemen, 2019)
This study aims to determine the financial performance of cigarette manufacturing companies listed on the BEI by using EVA analysis, and prove positive accounting earnings will have or do not have a positive EVA value. By using sample 4 (four) cigarette manufacturing companies listed on BEI, the result of this research mention that there are 3 of 4 or (75%) cigarette manufacturing companies listed on BEI experiencing EVA > 0 value, and profit positive accounting does not necessarily make the EVA value positive as well. This is due to an increase in the cost of equity capital that contributes the largest cost to the WACC figure which results in high capital charger borne by the company.